2008
DOI: 10.1177/0899764008320196
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Clients' Volunteering as a Means of Empowerment

Abstract: The population approaching social services for help is often characterized by poverty, passivity, helplessness, and an external locus of control. This population expects improvement in its situation but develops a dependent relationship with the help agents. The literature shows that volunteer work contributes toward developing empowerment among volunteers, but to date only a relatively small number of welfare clients have been activated as volunteers, serving more as the object of others' volunteer work. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Eleven papers reported RCTs (n = 7) [30,33,35,37,54,58,62] and non-RCTs (n = 4) [27,29,34,57]. As three RCT papers reported different outcomes collected at the same follow-up from the Experience Corps trial [30,35,58]; a total of five independent RCTs [33,37,54,62] were identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven papers reported RCTs (n = 7) [30,33,35,37,54,58,62] and non-RCTs (n = 4) [27,29,34,57]. As three RCT papers reported different outcomes collected at the same follow-up from the Experience Corps trial [30,35,58]; a total of five independent RCTs [33,37,54,62] were identified.…”
Section: Resultsmentioning
confidence: 99%
“…As three RCT papers reported different outcomes collected at the same follow-up from the Experience Corps trial [30,35,58]; a total of five independent RCTs [33,37,54,62] were identified. Of the non-RCTs [27,29,34,57], one paper was drawn from a small sample (n = 18) of Experience Corps trial participants [29] completing a comprehensive battery of cognitive tests that were not routinely administered in the wider cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Dolan, Peasgood, and White (2008) reviewed a wide range of economics literature and reached similar conclusions. Recent studies have continued to report the same link across different settings and research designs: longitudinal (Pillemer, Fuller-Rowell, Reid, & Wells, 2010;Siegrist & Wahrendorf, 2010;Tang, Choi, & MorrowHowell, 2010); mixed methods (O'Brien, Townsend, & Ebden, 2010); cross-national comparative (Haski-Leventhal, 2009); crosssectional (Borgonovi, 2008;Theurer & Wister, 2010); and experimental design (Cohen, 2009).…”
Section: Literature Reviewmentioning
confidence: 92%
“…In contrast, other researchers have found that volunteering makes welfare clients perceive themselves as active citizens, which bolsters their confidence and sense of control over their life (Cohen 2009;Koen 2013), with recognition from outside the labor market alleviating social marginality (Fuller et al 2008). …”
Section: Outcomes Of Workfare Volunteeringmentioning
confidence: 98%